A perovskite film for all-solid-state battery interface protection and preparation method thereof

By adding a perovskite film between the lithium metal negative electrode and the sulfide solid electrolyte, the problem of incompatibility of the layer of sulfide solid electrolyte and lithium metal is solved, and the circulation performance of the all-solid state battery is significantly improved.

CN115566189BActive Publication Date: 2025-02-18SHANGHAI FIRM LITHIUM NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211181736.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-27
Publication Date
2025-02-18
Estimated Expiration
2042-09-27

AI Technical Summary

Technical Problem

In the prior art, the solid electrolyte of layered sulfide is incompatible with lithium metal, resulting in serious side reactions, limiting its application in all-solid state batteries.

Method used

A perovskite film is added between the lithium metal negative electrode and the sulfide solid electrolyte, and the compatibility between the lithium metal negative electrode and the sulfide solid electrolyte is improved through the perovskite film medium.

Benefits of technology

Through the perovskite film medium, the compatibility of the lithium metal negative electrode and the sulfide solid electrolyte is significantly improved, and the circulation performance of all-solid state batteries is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115566189B_ABST
    Figure CN115566189B_ABST
Patent Text Reader

Abstract

The present invention relates to a perovskite film for all-solid-state battery interface protection and a preparation method thereof, which belongs to the field of solid-state batteries and solves the problem that sulfide solid electrolytes are incompatible with lithium metal. The perovskite material is MAQX3 (Q = Sn, Pb, Ge, Sb, Bi) (X = Cl, Br, I), which is an organic-inorganic hybrid perovskite material. MA represents methylammonium CH3NH3. This perovskite material has a highly directional framework with electrochemical stability and rapid lithium ion conduction. Under its protection, the metal chloride perovskite film can not only serve as an efficient solid electrolyte intermediate layer to induce ultra-dense deposition of Li, but also isolate Li metal from the electrolyte, providing a good environment for stable Li electroplating / stripping, and effectively inhibiting lithium loss and electrolyte decomposition during the cycle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of solid-state battery energy, and specifically relates to a perovskite film for all-solid-state battery interface protection and a preparation method thereof. Background Art

[0002] All-solid-state batteries use non-flammable solid electrolytes instead of traditional organic flammable electrolytes, which fundamentally avoids safety issues. At present, solid electrolytes mainly include oxides, sulfides, and polymer solid electrolytes. Among them, oxide solid electrolytes are not afraid of water and oxygen, have relatively stable physical and chemical properties, but have low electrical conductivity. Polymer solid electrolytes are formed by the complexation of polar polymers and metal salts, have good film-forming properties, are flexible and have high safety performance, but have low electrical conductivity, a small number of lithium ion migrations, and poor mechanical properties. Sulfide solid electrolytes have ionic conductivity comparable to that of liquid electrolyte solutions, a wide electrochemical window, and can be adapted to high-voltage positive electrode materials. However, since sulfide solid electrolytes have serious side reactions with lithium metal and are incompatible with lithium negative electrodes, their application in all-solid-state batteries is severely limited. Summary of the invention

[0003] The purpose of the present invention is to provide a perovskite film for all-solid-state battery interface protection and a preparation method thereof in view of the problem that the sulfide solid electrolyte in the prior art is incompatible with lithium metal. Sulfide solid electrolytes produce violent side reactions when used with lithium metal negative electrodes. By adding a layer of perovskite film between the lithium metal negative electrode and the sulfide solid electrolyte, the compatibility with the lithium metal negative electrode is greatly improved, and the cycle performance of all-solid-state batteries is better.

[0004] The chlorine-based perovskite material film of the present invention is used as the negative electrode interface layer to solve the problem that the sulfide solid electrolyte is incompatible with lithium metal. The perovskite material is MAQX3 (Q = Sn, Pb, Ge, Sb, Bi) (X = Cl, Br, I), which is an organic-inorganic hybrid perovskite material. MA represents methylammonium CH3NH3. This perovskite material has a highly directional framework with electrochemical stability and rapid lithium ion conduction. Under its protection, the metal chlorine perovskite film can not only serve as an efficient solid electrolyte intermediate layer to induce ultra-dense deposition of Li, but also isolate Li metal from the electrolyte, providing a good environment for stable Li electroplating / stripping, and effectively inhibiting lithium loss and electrolyte decomposition during the cycle. The other organic parts FA+ and Cs+ have ion size mismatch problems. The crystallization of the FA-Cs perovskite system will undergo a more complex intermediate phase transition process, thereby inducing lattice distortion, phase separation behavior and the appearance of defect centers, increasing the difficulty of preparing a uniform perovskite film. When the film used for interface protection is not uniform enough, it will affect the battery performance.

[0005] The purpose of the present invention can be achieved by the following scheme:

[0006] The present invention provides a perovskite film for all-solid-state battery interface protection. The perovskite film is an organic-inorganic hybrid material, the organic part is methylammonium (MA), and the molecular formula is MAQX3, wherein Q includes one or more of Sn, Pb, Ge, Sb, and Bi; and X includes one or more of Cl, Br, and I.

[0007] As an embodiment of the present invention, the thickness of the perovskite film is 2-50 μm. If the film is too thick, it will hinder the transmission of lithium ions, causing the transmission of lithium ions at the negative electrode interface to suddenly slow down, resulting in a larger interface impedance and affecting the performance of the entire battery. If the film is too thin, it may be broken down by the current and cannot play the role of negative electrode interface protection, resulting in internal short circuit failure of the battery.

[0008] The present invention also provides a method for preparing the perovskite film for all-solid-state battery interface protection, the preparation method comprising the following steps:

[0009] S1. Dissolving MAX and QCl2 in N,N-dimethylformamide (DMF) according to a molar ratio to form a MAQX3 precursor solution; Q includes one or more of Sn, Pb, Ge, Sb, and Bi; and X includes one or more of Cl, Br, and I;

[0010] S2, applying the precursor solution on the substrate;

[0011] S3. The coated sample is dried in vacuum to obtain the perovskite film for interface protection of all-solid-state batteries.

[0012] As an embodiment of the present invention, the concentration of the precursor solution in step S1 is controlled to be 1-1.5 M. The molar ratio of MAX to QCl2 is 3:1.

[0013] As an embodiment of the present invention, in step S2, the substrate is cleaned before coating and then dried for standby use; the drying temperature is 50-70°C and the time is 1-5h. When drying, it is necessary to select a suitable temperature to completely dry the solvent without affecting the subsequent battery assembly. The presence of the solvent will seriously affect the cycle life of the battery. Cleaning is carried out in an ultrasonic cleaning machine with deionized water, acetone and ethanol in sequence. The substrate thickness is 50-100μm and is a stainless steel foil.

[0014] As an embodiment of the present invention, in step S2, the precursor solution is coated on the substrate by spin coating; the spin coating speed is 2000-2500 rpm.min -1 , spin coating volume is 30-40μL / cm -2 .

[0015] As an embodiment of the present invention, the drying temperature in step S3 is 70-90°C and the drying time is 1-3 hours. After drying, the film is cooled to room temperature and taken out. During drying, in order to prevent the perovskite film from contacting moisture in the air as much as possible, the film needs to be cooled to room temperature before being taken out.

[0016] The present invention provides an all-solid-state battery, comprising a positive electrode part, an electrolyte part, a negative electrode part and the perovskite film, wherein the perovskite film is an intermediate layer between the electrolyte part and the negative electrode part.

[0017] As an embodiment of the present invention, the positive electrode part is constructed by mixing a positive electrode active material, a sulfide solid electrolyte and conductive carbon, and the positive electrode active material is a mixture of one or more of spinel transition metal oxides, layered lithium transition metal oxides, and olivine.

[0018] The present invention also provides a method for preparing an all-solid-state battery, the method comprising the following steps:

[0019] A1. Preparation of the intermediate layer-negative electrode sheet: The lithium sheet and the perovskite film are pressed to make the perovskite film adhere to the surface of the lithium metal, thereby obtaining a Li foil (MAQX3@Li foil) with a perovskite film, which is the intermediate layer-negative electrode sheet;

[0020] A2. Preparation of the positive electrode: The positive electrode material, conductive carbon black and sulfide solid electrolyte are mixed, ground and mixed evenly, dissolved in DME and coated on aluminum foil to obtain a positive electrode sheet;

[0021] A3. Battery assembly: Press the solid electrolyte powder into a coated solid electrolyte sheet, place the positive electrode sheet on one side of the coated solid electrolyte sheet, and press it with pressure. Finally, attach the middle layer - the negative electrode sheet to the other side of the coated solid electrolyte sheet and press it into a sandwich structured all-solid-state battery.

[0022] As an embodiment of the present invention, the pressing pressure in step A2 is 10-15 N.cm -2 , time is 60-90s.

[0023] Compared with the prior art, the present invention has the following advantages

[0024] (1) The present invention in situ coats a layer of solid electrolyte that is stable to lithium metal on the surface of the electrolyte, and the electrolyte selected has good electrical conductivity compared to traditional coating materials such as graphite.

[0025] (2) The process of the present invention is simple, efficient, low-cost, and suitable for commercial mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:

[0027] Figure 1 This is a long cycle diagram of an all-solid-state battery with a perovskite film interface prepared in Example 1 of the present invention;

[0028] Figure 2 This is a long cycle diagram of the all-solid-state battery assembled without the addition of perovskite film interface in comparative example 1 of the present invention. DETAILED DESCRIPTION

[0029] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. The following examples are implemented on the premise of the technical solution of the present invention, provide detailed implementation methods and specific operation processes, and will help those skilled in the art to further understand the present invention. It should be pointed out that the protection scope of the present invention is not limited to the following embodiments, and several adjustments and improvements made under the premise of the concept of the present invention all belong to the protection scope of the present invention.

[0030] Example 1

[0031] In a glove box, MACl and SnCl2 were weighed in a molar ratio of 1:1, and then these reactant raw materials were added into a round-bottom flask, and ultra-dry solvent DME was added to allow these raw materials to fully contact and react in the solvent to obtain MASnCl3 precursor slurry; 4 ml of MASnCl3 precursor slurry was spin-coated on a 10 cm × 10 cm stainless steel foil, vacuum dried, and pressed together with lithium foil to obtain MASnCl3@Li material.

[0032] The composite material of sulfide solid electrolyte material, positive electrode material, conductive carbon black and binder are mixed in a ratio of 20:75:1:4, and the positive electrode powder is obtained after grinding. The positive electrode powder is dissolved in DME, magnetically stirred and coated on aluminum foil. The powder of the coated sulfide solid electrolyte material is placed in a tablet pressing mold and pressed into a solid electrolyte sheet. Then, the positive electrode sheet is placed on one side of the solid electrolyte and pressed under pressure. Finally, MASnCl3@Li is attached to the other side of the solid electrolyte and pressed into an all-solid-state battery.

[0033] The long cycle life of the all-solid-state battery prepared in this embodiment is as follows Figure 1 As shown. The assembled all-solid-state battery has almost no capacity decay after 50 cycles at a rate of 0.2C, from 165mAh g -1 155mAh g -1 .

[0034] Example 2

[0035] In a glove box, MACL and PbCl2 were weighed in a molar ratio of 1:1, and then these reactant raw materials were added into a round-bottom flask. Ultra-dry solvent DME was added to allow these raw materials to fully contact and react in the solvent to obtain MASnCl3 precursor slurry; 4 ml of MAPbCl3 precursor slurry was spin-coated on a 10 cm × 10 cm stainless steel foil, vacuum dried, and pressed together with lithium foil to obtain MAPbCl3@Li material.

[0036] The composite material of sulfide solid electrolyte material and positive electrode material is mixed with conductive carbon black and binder in a ratio of 20:75:1:4, and the positive electrode powder is obtained after being evenly ground. The positive electrode powder is dissolved in DME, magnetically stirred and coated on aluminum foil. The powder of the coated sulfide solid electrolyte material is placed in a tablet pressing mold and pressed into a solid electrolyte sheet. Then the positive electrode sheet is placed on one side of the solid electrolyte and pressed under pressure. Finally, MASnCl3@Li is attached to the other side of the solid electrolyte and pressed into an all-solid-state battery.

[0037] Example 3

[0038] In a glove box, MACl and GeCl2 were weighed in a molar ratio of 1:1, and then these reactant raw materials were added into a round-bottom flask. Ultra-dry solvent DME was added to allow these raw materials to fully contact and react in the solvent to obtain MAGeCl3 precursor slurry; 4 ml of MASnCl3 precursor slurry was spin-coated on a 10 cm × 10 cm stainless steel foil, vacuum dried, and pressed together with lithium foil to obtain MAPbCl3@Li material.

[0039] The composite material of sulfide solid electrolyte material and positive electrode material is mixed with conductive carbon black and binder in a ratio of 20:75:1:4, and the positive electrode powder is obtained after being ground evenly. The positive electrode powder is dissolved in DME, magnetically stirred evenly and then coated on aluminum foil. The powder of the coated sulfide solid electrolyte material is placed in a tablet pressing mold and pressed into a solid electrolyte sheet. Then the positive electrode sheet is placed on one side of the solid electrolyte and pressed under pressure. Finally, MAGeCl3@Li is attached to the other side of the solid electrolyte and pressed into an all-solid-state battery.

[0040] Comparative Example 1

[0041] The surface of the lithium metal negative electrode in this comparative example is not treated in any way, and the rest is the same as in Implementation Example 1.

[0042] The long cycle life of the prepared all-solid-state battery Figure 2 As shown. Without any protection for the interface, the all-solid-state battery was assembled. At a low rate of 0.1C, the second cycle of the battery short-circuited.

[0043] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. An all-solid-state battery, characterized in that: It includes a positive electrode part, an electrolyte part, a negative electrode part and a perovskite film, wherein the perovskite film is an intermediate layer between the electrolyte part and the negative electrode part and is used for interface protection of an all-solid-state battery; The perovskite film is an organic-inorganic hybrid material, the organic part is methylammonium, and the molecular formula is MAQX3, wherein MA is methylammonium, Q includes one or more of Sn, Pb, Ge, Sb, and Bi; and X includes one or more of Cl, Br, and I; The electrolyte is a sulfide solid electrolyte.

2. The all-solid-state battery according to claim 1, characterized in that: The thickness of the perovskite film is 2-50 μm.

3. The all-solid-state battery according to claim 1, characterized in that: The method for preparing the perovskite film comprises the following steps: S1. Dissolve MAX and QCl2 according to a molar ratio to form a MAQX3 precursor solution; Q includes one or more of Sn, Pb, Ge, Sb, and Bi; and X includes one or more of Cl, Br, and I; S2, applying the precursor solution on the substrate; S3. The coated sample is vacuum dried to obtain a perovskite film for interface protection of all-solid-state batteries.

4. The all-solid-state battery according to claim 3, characterized in that: The concentration of the precursor solution in step S1 is 1-1.5 M.

5. The all-solid-state battery according to claim 3, characterized in that: In step S2, the base liner is cleaned before coating and then dried for standby use; the drying temperature is 50-70° C. and the drying time is 1-5 h.

6. The all-solid-state battery according to claim 3, characterized in that: In step S2, the precursor solution is applied to the substrate by spin coating; the spin coating speed is 2000-2500 rpm.min -1 , spin coating volume is 30-40 μL / cm -2 .

7. The all-solid-state battery according to claim 3, characterized in that: The drying temperature in step S3 is 70-90°C and the drying time is 1-3 h.

8. A method for preparing an all-solid-state battery as claimed in claim 1, characterized in that: The preparation method comprises the following steps: A1. Preparation of the intermediate layer-negative electrode sheet: Pressing the lithium sheet and the perovskite film so that the perovskite film adheres to the surface of the lithium metal, thereby obtaining a Li foil with the perovskite film, which is the intermediate layer-negative electrode sheet; A2. Preparation of the positive electrode: The positive electrode material, conductive carbon black and sulfide solid electrolyte are mixed, ground and mixed evenly, dissolved in DME and coated on aluminum foil to obtain a positive electrode sheet; A3. Battery assembly: Press the solid electrolyte powder into a coated solid electrolyte sheet, place the positive electrode sheet on one side of the coated solid electrolyte sheet, and press it with pressure. Finally, attach the middle layer - the negative electrode sheet to the other side of the coated solid electrolyte sheet and press it into a sandwich structured all-solid-state battery.

9. The method for preparing an all-solid-state battery according to claim 8, characterized in that: The pressing pressure in step A2 is 10-15 N.cm -2 , time is 60-90 s.

Citation Information

Patent Citations

  • Photocathode and solar cell with same

    CN104409217A